Pengaruh Komposisi Elektrolit pada Proses Penyisihan Nikel dari Tiruan Air Limbah Elektroplating Menggunakan Sel Elektrodeposisi Dua Ruang - Selly Ayu Janetasari; Djaenudin Djaenudin (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2019)
Research of removal of soluble nickel from artificial electroplating wastewater has been investigated. The research aim to know optimum electrolit composition in nickel electrodeposition process. This study was conducted within a batch system using double chamber electrodeposition cell separated by water hyacinth leaf. Electrodeposition cell was equipped with a copper plate as cathode, graphite plate as anode, H2SO4 anolyte, NiSO4 catholyte with Na2SO4 added as supporting electrolyte. Electrodeposition performed at 5V direct current voltage for 4 hours each running and varied the concentration of H2SO4 anolyte (0,2 M; 0,6 M and 1 M), pHinitial catholyte (2; 4 and 6) and Na2SO4 (catholyte) supporting electrolyte (0 M; 0,2 M; 0,6 M and 1 M). The statistic analysis results showed that the concentration of 0.2 M H2SO4, pHinitial catholyte of 6 and 0.2 M Na2SO4 with an optimum concentration of nickel concentration values decrease of 18,433 % and nickel deposition on the cathode of 0.042 grams.